Complexity in international security : a holistic spatial approach - Sapaty, Peter Simon (Emerald Publishing Limited, 2019)
In September 2018, the 73rd General Assembly of the United Nations acknowledged that international instability is increasing and that improving global security is among the most important tasks facing the world today. The Assembly concluded that it is extremely important to develop new, effective frameworks and technologies to understand and confront increasingly complex networks of actors, interests, and contexts. Leading international security expert Peter Sapaty meets this challenge head-on and introduces a new, high-level distributed processing and control approach capable of finding real-time solutions for irregularities, crises, and security problems emerging any time and in any part of the world. Drawing upon the principles of Gestalt psychology, this book develops a radically new model of technology, Spatial Grasp Technology (SGT), a self-navigating, self-replicating, self-modifying spatial pattern technology expressed in a special high-level recursive language. Through rigorous theoretical argument and many practical examples, Sapaty shows how SGT can account for millions to billions of nodes distributed worldwide without vulnerable central resources; explains why SGT is hundreds of times shorter, simpler, and faster than other models and languages; and shows that SGT's technology basics are so simple that they can be effectively implemented even in a short time by a small group of system programmers within traditional university environments. Perhaps most importantly, Sapaty demonstrates how SGT is capable of implementing security scenarios not only at run time, but also conceivably ahead of it, allowing in some cases for the prediction and even prevention of local or global crises. For the novelty, simplicity, and wide applicability of its approach, Complexity in International Security is essential reading for system scientists, application programmers, industry managers, security and defence personnel, and university students interested in advanced MSc and PhD projects in the area of holistic and distributed management.